Cujo - King, Stephen, 1947- (New York : Signet, 1982)
Cujo, a two-hundred-pound Saint Bernard, becomes infected with rabies and kills four people in Maine.
Kirkus Review.
School Library Journal.
Wilson's Fiction.
Adult.
Adult
Keywords: Saint Bernard dog -- Fiction; Dogs -- Fiction; Horror fiction; Saint Bernard dogs -- Fiction; Maine -- Fiction; Maine -- Fiction